The Importance of Leadership, Organizational Culture, and Work Environment against the Employee Performance of BPJS Kesehatan in Karawang Branch Office Business - Muttaqin, Mohammad Fajar; Hersona, Sonny; Hartelina, Hartelina (Dinasti Publisher, 2023)
This research aims to explore and reveals the effect cause by leadership, organizational culture, and work environment towards the performance of BPJS Kesehatan’s employees at Karawang Branch Office. Descriptive and verification method has been used in this study through quantitative approach. The research population of this study amounted to 126 people, while the sample used was 100 respondents who were exactly the employees of BPJS kesehatan at Karawang Branch Office which selected by simple random sampling technique. Data research was gathered through questionnaire which then analyzed using scale range analysis and path analysis. The results of this research indicates that 1) There is influence occurred between leadership and organizational culture that categorize as low level of correlation with positive value 2) There is correlation between organizational culture and work environment which categorize as low level of correlation and positive value 3) There is correlation between leadership and work environment which categorize as low level of correlation with positive direction 4) leadership, work culture, and work environment are capable to improve the performance of BPJS Kesehatan employees at Karawang Branch Office both partially or simultaneously.